Metal concentration and environmental risk assessment of roadside soils in highly urbanized areas of Bukidnon, Philippines - JOHN REY NATINGA LABAJO; JUNESA UDTOJAN CRISTOBAL; MYRNA GEMENTIZA PABIONA; ROMIL S. TAN; JESSIE GUTIERREZ-SUSON; LYDIA EBARE-TIONGCO (Smujo International, 2025)
Abstract. Labajo JRN, Cristobal JU, Pabiona MG, Tan RS, Gutierrez-Suson J, Ebare-Tiongco L. 2025. Metal concentration and environmental risk assessment of roadside soils in highly urbanized areas of Bukidnon, Philippines. Nusantara Bioscience 17: 68-83. Five urbanized localities in Bukidnon were selected based on population density and vehicular activities. Soil samples were collected, and metal concentration was determined using AAS, sediment quality guidelines, and the contamination index. The study assessed the metal concentration and environmental risk assessment of soil along the road from five localities in the Province of Bukidnon: It was observed that the highest total concentration for Mn (229.46±21.26), Fe (199.87±51.78), Co (38.13±16.18), Zn (32.43±19.13), Cu (18.17±4.52), Cr (17.95±1.76), and Cd (0.901±0.063) mg kg-1 respectively, Mn, exhibited the highest (lgeo), of